2001
DOI: 10.1128/jvi.75.24.12431-12438.2001
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein K Specified by Herpes Simplex Virus Type 1 Is Expressed on Virions as a Golgi Complex-Dependent Glycosylated Species and Functions in Virion Entry

Abstract: Herpes simplex virus type 1 (HSV-1) specifies at least 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 45 publications
3
85
0
Order By: Relevance
“…Indeed, Loret et al confirmed the presence of 12 of these proteins in mature virions (68). Some reports have detected UL53 in mature virions (69,70), whereas others did not (71). UL3 was identified in our data at the late time points of HSV-1 infection (9 -15 hpi).…”
Section: Fig 1 Proteome Characterization During Hsv-1 Infection By mentioning
confidence: 91%
“…Indeed, Loret et al confirmed the presence of 12 of these proteins in mature virions (68). Some reports have detected UL53 in mature virions (69,70), whereas others did not (71). UL3 was identified in our data at the late time points of HSV-1 infection (9 -15 hpi).…”
Section: Fig 1 Proteome Characterization During Hsv-1 Infection By mentioning
confidence: 91%
“…Virus HSV-1 (KOS) d27-1, which has a 1.6-kb BamHI-StuI deletion of the ICP27 gene, was kindly provided by D. M. Knipe, Harvard Medical School, and was propagated in complementing V27 cells (39). The UL53-gK protC epitope-tagged virus (gKprotC) was propagated in Vero cells and was as described previously (14).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…1). The recombinant gK genes coding for the epitope-tagged gKs were constructed by using PCR-based splice-overlap extension methodology as described previously except that either HSV-1 KOS gK or HSV-1 KOS gKsyn20 DNA was used as a template (14). The KOS gKsyn20 DNA specifies a single amino acid substitution at amino acid 40 of gK (Ala to Val) that results in extensive virus-induced cell-to-cell fusion.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 2 more Smart Citations